A memristive chaotic oscillator with controllable amplitude and frequency. (October 2020) - Zhang, Xin; Li, Chunbiao; Chen, Yudi; IU, Herbert H.C.; Lei, Tengfei
Highlights: By introducing a memristor in a 3-D variable-boostable system, a chaotic system with an amplitude-frequency controller is derived. The memristive chaotic system exhibits relatively robust chaotic oscillation compared with other multistable systems. Internal parameter of a memristor leaves a new opportunity for easy amplitude/frequency, where no extra circuits are needed. Abstract: Broadband frequency property of chaos stands in the way of application. Internal parameter of a memristor leaves a new opportunity for easy amplitude/frequency control. Based on a variable-boostable chaotic system, such an amplitude-frequency controllable chaotic system is derived, which exhibits relatively robust chaotic oscillation compared with other multistable memristive systems. Furthermore, the controllable chaotic system gives a symmetric pair of oscillations, which finally merges to be a single symmetric one. Circuit experiment based on STM32 agrees well with the systematic analysis and numerical simulation.